Relação entre os estilos parentais e o desempenho intelectual de crianças com pumblemia - Dascanio, Denise; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Valle, Tania Gracy Martins do [UNESP] (My University, 2010)
This study investigated the children s intellectual development with high and low blood lead level with the parenting styles in the respective interactions with these children. The WISC-III and IEP (Parenting Styles Inventory) were used. Were studied 40 children, with ages among 7 to 13 years old, and 40 parents, who lived in a risk spot near the contamination area. The children were divided into two groups: G1 – 20 children with blood lead level above 10µg/dl; and G2 – 20 children with blood lead level lower than 10µg/dl. The results indicated damages on WISC-III for the children with Pb-S than10µg/dl and prevalence of practices educational negatives were found in both groups, with statistical difference (5%). The environmental stimulation can minimize the damages caused by the lead poisoning, and the parent s positive educative practice can contribute as modulator of the lead s effect.

Este artigo investigou a relação entre o desempenho intelectual de crianças com alta e baixa plumbemia e os estilos parentais maternos. Utilizou-se o WISC-III e o IEP. Participaram do estudo 40 crianças, com idades entre 7 e 13 anos, e 40 pais, todos moradores da área de risco próximo ao local de contaminação. As crianças foram divididas em dois grupos: G1 – 20 crianças com alta plumbemia (superior a 10µg/dl); e G2 – 20 crianças com baixa plumbemia (inferior a 10 µg/dl). Os resultados apontaram prejuízos no WISC-III para as crianças com Pb-S superior a 10 µg/dl e predomínio de práticas educativas negativas foi encontrado em ambos os grupos, com significância estatística ao nível de 5%. Tais resultados sugerem que um ambiente com fontes de estimulação pode minimizar os prejuízos causados pela contaminação, sendo que as práticas educativas dos pais poderiam contribuir, tendo uma influência moduladora dos efeitos do chumbo.
Relationship between parenting styles and intellectual development in the children'swith blood lead level
Keywords: Poisoning; Infantile development; Parenting styles; Intoxicação; Desenvolvimento infantil; Estilos parentais